Cognitive Testing of Items Measuring Movement Behaviours in Young Children Aged Zero to Five Years: Development of the Movement Behaviour Questionnaires for -Baby (MBQ-B) and -Child (MBQ-C) - Rebecca Byrne; Caroline O. Terranova; Li Kheng Chai; Denise S. K. Brookes; Stewart G. Trost (MDPI AG, 2023)
This paper describes the cognitive interview phase of the development of two brief surveys, the Movement Behaviour Questionnaire-Baby (MBQ-B) and Movement Behaviour Questionnaire-Child (MBQ-C), which measure the duration of physical activity, screen time, and sleep of children aged 0-5 years. The aims were (1) review the format, content, and clarity of questionnaire items and response options, (2) understand how parents retrieve, encode, and formulate responses when asked about their child's movement behaviours, and (3) identify potential sources of response error and make appropriate modifications. Interviews with parents of children aged 0-5 years were conducted using concurrent think-aloud techniques and probing questions. Parents reviewed the MBQ-B and/or MBQ-C depending on the developmental stage of their child(ren). Twenty-nine interviews were conducted with 20 parents, over four iterative rounds. Participants recalled usual family routines and rules when estimating the duration/frequency of behaviours. To estimate active play, parents referred to the child's daily routine considering wake and bedtimes, naps, and mealtimes. Participants were influenced by the examples provided, being unable to interpret these as exemplars only. Decomposing general items into specific questions with examples was well received. Use of numeracy skills when estimating duration was evident. Interviews informed revisions to item wording, examples, and recall prompts, which will be taken forward into the MBQ-B and MBQ-C validation studies. Utilising cognitive interviewing can enhance confidence that questionnaire items are correctly interpreted and understood by participants.